Analisis Pengelolaan Limbah B3 dengan Metode Root Cause Analysis (RCA) di RSUD Jayapura - Hananto Rahmad Suselo; Prasidananto Nur; Esa Rengganis (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Jayapura Hospital is the main referral hospital in Papua and plays an important role in public health services. The management of hazardous and toxic (B3) waste at this hospital still faces various obstacles, including the lack of waste segregation by type, limited storage facilities and infrastructure, and a suboptimal monitoring and evaluation system. These conditions contribute to work accidents among medical personnel, such as needlestick injuries and exposure to infectious waste. This study uses the qualitative Root Cause Analysis (RCA) method to identify the root causes of non-compliance in B3 waste management that lead to these problems and accidents at Jayapura Hospital. The results show that the B3 medical waste management process at Jayapura Hospital is not yet in accordance with the Regulation of the Ministry of Environment and Forestry No. 56 of 2015 on technical requirements and procedures for B3 waste management from healthcare facilities. Waste reduction and segregation are identified as key components in B3 medical waste management. The main contributing factors to the problems are the lack of staff compliance and awareness regarding Standard Operating Procedures (SOPs), especially in the segregation of sharp waste and the use of personal protective equipment (PPE), compounded by inadequate facilities such as limited safety box availability and weak supervision and management commitment.